The harmonic characteristics analysis of offshore wind farms transmitted by the submarine cable based on time domain simulation. Issue 1 (April 2021) - Li, Jingyi; Yang, Jianjun; Shi, Zhaohui; Wang, Ke; Li, Haozhi; Xie, Xiaorong; Li, Fangfeng
Abstract: The harmonic amplitude may exceed the limit when the large scale of wind farm is connected to the weak AC system through AC submarine cable. The harmonic with high amplitude will endanger the safety of power equipment, and even affect the normal integration of large-scale wind farm. This paper takes an actual offshore wind power connected to the system through AC submarine cable as an example. On the basis of building the model of the system in the PSCAD/EMTDC simulation software. The simulation calculation is systematically carried out. The effect of multiple factors on the harmonic characteristics is analyzed. The preliminary explanation for the harmonic amplitude out of limit is given for the actual large scale of wind farm connected to the weak AC system through AC submarine cable.